Preparation method and application of nanocellulose aerogel photocatalyst
By preparing a uniformly distributed p-n-type titanium dioxide-bismuth trioxide heterojunction photocatalyst on a nanocellulose aerogel support, the problems of low degradation efficiency of antibiotic pollutants and the generation of secondary pollutants in the prior art are solved, and the problem of low degradation efficiency of antibiotic pollutants and the generation of secondary pollutants in the prior art is achieved. Highly efficient photocatalytic degradation effect.
Patent Information
- Application Number
- CN202410986120.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-22
- Publication Date
- 2025-01-03
AI Technical Summary
The prior art has problems with low efficiency and secondary pollutants in degrading antibiotic pollutants in water bodies, especially the difficulty in removing tetracycline, and insufficient design and regulation of nanostructures, resulting in disordered multi-structures and the impossibility of achieving the optimal effective contact area. .
Using nanocellulose aerogel as a support, a uniformly distributed p-n type titanium dioxide-bismuth trioxide heterojunction photocatalyst was prepared by electrostatic self-assembly and chemical crosslinking to form a composite material, and aerogel was obtained by freeze-drying. Structure, improve photocatalytic efficiency.
The efficient photocatalytic degradation of antibiotic wastewater is achieved, the separation efficiency of photogenerated electron-hole pairs is improved, the electron-hole recombination is inhibited, the photocatalytic efficiency and dispersion are improved, and the degradation ability of tetracycline is significantly improved.
Smart Images

Figure HSA0000299614950000011 
Figure HSA0000299614950000012 
Figure HSA0000299614950000021
Abstract
Description
Technical Field
[0001] The invention belongs to the field of biomass aerogel materials, and in particular relates to a preparation method and application of a nanocellulose aerogel catalyst containing a pn heterojunction. Background Art
[0002] Water pollution is one of the most serious environmental problems at present, and the problem of antibiotic wastewater is particularly prominent. Due to people's dependence on antibiotics, antibiotic residues are detected in more and more water bodies. Tetracycline is the second most used antibiotic in the world. Due to its hydrophilicity and accumulation, it is difficult to remove it from water.
[0003] Currently known water treatment methods include biological treatment and physical treatment. Photocatalytic technology has attracted much attention because it can completely degrade pollutants and effectively reduce the generation of secondary pollutants. Compared with traditional processes, photocatalytic technology has many advantages in degrading antibiotic pollutants in water bodies. For example, it uses sunlight to degrade antibiotics, can reduce the generation of secondary pollutants, and has low manufacturing costs. In the family of photocatalysts, heterostructured photocatalysts have attracted much attention due to their potential to completely oxidize organic pollutants and inactivate microorganisms. Heterojunction photocatalysts have been favored by many researchers. Multi-pn heterostructures have become the preferred design structure for high-performance photocatalysts due to their large specific surface area, efficient charge separation, and rapid charge transfer. However, most previous reports have focused on the simple integration of multi-pn photocatalysts without reasonable design and regulation of nanostructures, resulting in disordered multi-pn structures and the inability to achieve optimal effective contact area.
[0004] Nanocellulose is abundant in sources and is a green and environmentally friendly material. Cellulose materials are widely used in adsorption, energy storage, conductive devices, catalysis, biomedicine and other fields. Nanocellulose has excellent adsorption properties for antibiotic pollutants and is also an excellent catalyst carrier. Cellulose composite photocatalysts have the advantages of good adsorption performance, strong ability to remove pollutants, strong recycling ability, and environmental friendliness, and are increasingly attracting attention.
[0005] As a good adsorption material, aerogel has many advantages such as low density, high specific surface area, and good adsorption capacity for various pollutants. The emergence of various water pollution problems, such as petroleum, dyes, heavy metal ions, gases, particulate matter, salts, drugs, etc., has made aerogels attract much attention in the field of water treatment.
[0006] Nanocellulose aerogels have the advantages of good biocompatibility and easy chemical modification. At present, some studies have reported composite materials of cellulose nanofibers and photocatalysts, which are mainly used for photocatalytic degradation of dyes. TiO2-Bi2O3 was loaded onto CNFs aerogel to prepare a material with both adsorption and photocatalytic functions, which also overcomes many shortcomings of powder materials. There are no reports of CNFs combined with TiO2-Bi2O3 photocatalysts for photocatalytic degradation of tetracycline. The preparation of this composite material improves the performance of semiconductor photocatalysts in degrading TC and accelerates the separation of photogenerated electron-hole pairs. Summary of the invention
[0007] In view of the exploratory problems existing in the existing theories, the purpose of the present invention is to provide a pn heterojunction photocatalytic material with nanocellulose aerogel as a carrier, and a preparation method and application thereof.
[0008] The present invention is achieved through the following technical solutions:
[0009] The invention provides a nano-cellulose aerogel composite material, comprising uniformly distributed pn-type heterojunction titanium dioxide-bismuth trioxide.
[0010] Furthermore, the nanocellulose is made by pure mechanical grinding and is rich in hydroxyl groups.
[0011] Furthermore, in the uniformly distributed heterojunction, the mass ratio of bismuth to titanium is 1:1, 1:2, 1:3, 2:1 and 3:1.
[0012] Furthermore, the mass percentage of the heterojunction to the nanocellulose is: 50%, 100% and 200%.
[0013] Furthermore, the preparation of the composite material of the present invention comprises the following steps:
[0014] (1) The bismuth precursor is first loaded onto a titanium dioxide support by an electrostatic self-assembly method, and a heterojunction is obtained by hydrothermal synthesis;
[0015] (2) cross-linking the heterojunction to the nanocellulose by chemical cross-linking to obtain a composite material;
[0016] (3) Freeze-drying the composite material into aerogel in a freeze dryer.
[0017] Furthermore, in step (1), the mass ratio of the bismuth precursor to titanium dioxide is 1:1, 1:2, 1:3, 2:1, or 3:1.
[0018] Furthermore, bismuth nitrate pentahydrate was dispersed in deionized water, anatase titanium dioxide was added and magnetically stirred for 24 hours, and then the mixture was dried and calcined at a high temperature of 400° C. for 5 hours.
[0019] Furthermore, in step (2), the nanocellulose is a nanocellulose aqueous solution with a concentration of 0.65-1 wt%; a certain PVA solution is added with a concentration of 0.05 g / mL; glutaraldehyde is a cross-linking agent with a volume of 5-10 mL.
[0020] Furthermore, the nanocellulose solution and the PVA solution were mixed and stirred for 1 h, the glutaraldehyde solution was added and stirred for another 1 h, and then the heterojunction dispersion was added dropwise, cross-linked for 3 h, and washed three times by centrifugation with deionized water.
[0021] Furthermore, in step (3), the pretreatment temperature is -196°C for 5-7 min; the freeze-drying temperature is -(50-60)°C for 24-30 h.
[0022] The nanocellulose aerogel composite material of the present invention can be well applied to photocatalytic degradation of antibiotic wastewater.
[0023] The nanocellulose aerogel composite material of the present invention is used for photocatalytic degradation of antibiotic wastewater. The composite material is put into a tetracycline solution, the concentration of the tetracycline solution is 10-40 mg / L, the dosage of the composite material is 10, 30, 50 and 70 mg, and the tetracycline solution is stirred under the irradiation of an ultraviolet light source to perform a photocatalytic degradation reaction; the ultraviolet light source used is a xenon lamp.
[0024] Under the above conditions, the composite material of the present invention exhibits excellent catalytic performance in the ultraviolet light catalytic degradation of antibiotic wastewater, with the following specific advantages:
[0025] (1) The composite material designed by the present invention is ultra-light and porous, and is easy to chemically modify, which is beneficial to the migration of photogenerated carriers and has a better catalytic effect;
[0026] (2) The nanocellulose used in the present invention can inhibit the agglomeration of heterojunction powders, improve the dispersibility of the composite material, and facilitate full contact with organic pollutants;
[0027] (3) The formation of the heterojunction interface inhibits the recombination of electrons and holes, and the photocatalytic efficiency of the heterojunction is higher than that of two individual semiconductors, titanium dioxide and bismuth trioxide. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 Schematic diagram of the preparation process of the composite material of the present invention
[0029] Figure 2 XRD pattern of the nanocellulose aerogel composite material prepared in Example 1
[0030] Figure 3 Schematic diagram of the photocatalytic degradation of tetracycline in Example 2
[0031] Figure 4 Schematic diagram of photocatalytic results of heterojunctions with different ratios in Example 3
[0032] Figure 5 Schematic diagram of the photocatalytic results of different heterojunction contents in Example 4
[0033] Figure 6 The photocatalytic results of tetracycline at different pH values in Example 5 are shown in FIG.
[0034] Figure 7 Schematic diagram of the photocatalytic results of different initial concentrations of tetracycline in Example 5
[0035] Figure 8 Schematic diagram of photocatalytic results at different dosages of the composite material in Example 5
[0036] Fig. 9 Schematic diagram of free radical capture experiment in Example 6
[0037] Fig.10 The photoluminescence (PL) spectrum of Example 7 is shown in FIG. DETAILED DESCRIPTION
[0038] The present invention is further described in detail below by way of examples. These examples are only used to illustrate the present invention and do not limit the protection scope of the present invention.
[0039] The invention provides a nano-cellulose aerogel composite material, characterized in that it comprises uniformly distributed pn-type heterojunction titanium dioxide-bismuth trioxide.
[0040] The composite material used in the present invention includes cellulose nanofibers as aerogel carriers, provided by Flash Technology Co., Ltd., which have a high aspect ratio, large specific surface area, and rich hydrogen bonds on the surface. The freeze-cast nanocellulose aerogel has layered pores and high water absorption capacity.
[0041] The composite material provided by the present invention also includes a titanium dioxide-bismuth trioxide heterojunction; the mass ratio of the heterojunction powder to the nanocellulose carrier is preferably 50-200%, more preferably 50%, 100% and 200%, and finally preferably 100%.
[0042] The composite material provided by the present invention comprises titanium dioxide and bismuth trioxide; the mass ratio of bismuth trioxide to titanium dioxide is preferably 1-3:3-1, more preferably 1:1, 1:2, 1:3, 3:1 and 2:1, and finally preferably 1:2.
[0043] Example 1
[0044] The nanocellulose aerogel composite material is prepared by the following steps:
[0045] Weigh 100 mg of bismuth nitrate pentahydrate and dissolve it in 100 mL of deionized water. Stir well and add 100 mg of commercial titanium dioxide, which has anatase crystal form. Stir magnetically for 24 hours and pour it into a petri dish. Dry it at 60°C for 24 hours. Place the dried powder in a magnetic boat and calcine it at 400°C for 5 hours. After cooling at room temperature, a light yellow heterojunction powder is obtained.
[0046] Weigh 0.13g of nanocellulose powder and disperse it in 10mL of deionized water. Ultrasonicate to make it uniformly dispersed. Prepare 2ml of 0.05g / mL PVA solution and pour it into the above nanocellulose dispersion. Add 10mL of deionized water and stir magnetically for 1h. Then add 5mL of pH=4 glutaraldehyde solution and continue stirring for 1h to obtain solution a. Disperse the heterojunction powder obtained above in 20mL of deionized water to obtain solution b. Add b drop by drop into solution a and stir continuously for 3h to obtain a light yellow flocculent precipitate. Wash it with deionized water by centrifugation 3 times.
[0047] The precipitate obtained above was dissolved in 20 mL of water, and after being completely dispersed, it was pretreated with -196°C liquid nitrogen for 5-7 min, and then placed in a freeze dryer at -(50-60)°C for freeze drying for 24-30 h to obtain a nanocellulose aerogel composite material. The complete preparation process is as follows Figure 1 .
[0048] Figure 2 is the XRD spectrum of the composite material. It can be seen from the figure that the XRD diffraction peak of the composite material is consistent with the diffraction peak of the heterojunction, and has obvious CNFs characteristic peaks, indicating that the catalyst with nanocellulose as the carrier is successfully prepared.
[0049] Example 2
[0050] Tetracycline photocatalytic degradation reaction:
[0051] A xenon lamp was used as the light source, and the photocatalytic effect was monitored by the absorbance of the reaction solution. A UV-visible spectrometer was used to scan the entire 300-400nm region of the sample. In order to conduct a preliminary experiment, 30 mg of aerogel composite material was first added to the photoreactor, and then 100 mL of a tetracycline solution with a concentration of 10 mg / L was added. After ultrasonic dispersion, it was placed on a magnetic stirrer and adsorbed and stirred for 30 minutes in a dark environment to reach adsorption equilibrium. The sampling mark was 0. This step was to exclude the adsorption of pollutants by aerogels in a dark environment. Then the xenon lamp was turned on and the timing was started. Samples were taken every 10 minutes until the reaction was stopped after 1 hour. The removed samples were filtered with a 0.22μm filter membrane and then the absorbance test was performed. The degradation rate and degradation rate constant obtained are shown as follows Figure 3 shown.
[0052] Example 3
[0053] Comparative experiment of different ratios of heterojunction:
[0054] The dosage of bismuth nitrate pentahydrate and titanium dioxide in Example 1 was changed to obtain heterojunction bismuth trioxide and titanium dioxide with a mass ratio of 1:1, 1:2, 1:3, 2:1 and 3:1, respectively. The photocatalytic degradation experiment of Example 2 was repeated for aerogel composite materials with different heterojunction ratios, and the degradation rate graph obtained was shown in the figure. Figure 4 It can be seen that the photocatalytic degradation effect is best when the mass ratio of bismuth trioxide to titanium dioxide is 1:2.
[0055] Example 4
[0056] Comparative experiment of heterojunction with different contents on nanocellulose:
[0057] The concentration of solution b in Example 1 was changed by increasing the amount of heterojunction powder dispersed in deionized water, so that the heterojunction powder accounted for 50%, 100% and 200% of the nanocellulose carrier. The photocatalytic degradation experiment of Example 2 was repeated, and the degradation rate was shown in the figure. Figure 5 It can be seen that the degradation effect is best when the heterojunction accounts for 100% of the nanocellulose carrier.
[0058] Example 5
[0059] Condition optimization experiment:
[0060] The pH of the tetracycline solution in Example 2 was changed by using 0.1 M dilute hydrochloric acid. The present invention investigated the photocatalytic degradation of tetracycline at pH 3, 5, 7, and 9. Figure 6 It can be seen that the degradation effect of tetracycline is best when the pH is 7.
[0061] Changing the concentration of tetracycline solution to explore the effect of concentration on the degradation rate of the composite material and the optimal concentration for subsequent characterization. Figure 7 It can be seen that the composite material can degrade tetracycline at different concentrations, and the degradation effect is most obvious when it is 10 mg / L.
[0062] The dosage of the composite material was changed each time the photocatalytic degradation was performed. When the dosage was 30 mg, the degradation rate was the highest. Figure 8 shown.
[0063] Example 6
[0064] Free radical capture experiment:
[0065] There are three groups in tetracycline: double bonds, amine groups, and phenol groups, which are easily attacked by free radicals and release many intermediates during the reaction. In order to explore the possible photocatalytic degradation mechanism, a free radical capture experiment was conducted, and a blank control group was set up to ensure the reliability of the experiment. Fig. 9 As shown in the figure, after 60 minutes of illumination, the addition of capture agents BQ and EDTA-2Na significantly inhibited the photocatalytic degradation efficiency of the composite material, and the addition of IPA reduced the photocatalytic degradation of the composite material, but not significantly. + and ·O2 play a major role in the photocatalytic degradation of tetracycline, while the role of ·OH is relatively small.
[0066] Example 7
[0067] Photoluminescence (PL) spectroscopy characterization:
[0068] The photoluminescence spectrum produced by the recombination of photogenerated electron-hole pairs can be used to study the sample carrier capture, migration and transfer behavior. The PL spectrum is used to study the migration behavior of photogenerated charges in the composite material during the photocatalytic process, where a lower PL spectrum intensity indicates a lower carrier recombination rate. Fig.10 As shown, the PL intensity of the composite material is weakened due to the presence of the pn heterojunction, indicating that the pn heterojunction can significantly inhibit the recombination of photogenerated electrons and holes.
Claims
1. A nanocellulose aerogel composite material comprising uniformly distributed pn-type heterojunction titanium dioxide-bismuth trioxide.
2. The nanocellulose aerogel composite material according to claim 1, characterized in that The nanocellulose used is made by pure mechanical grinding and is rich in hydrogen bonds and hydroxyl groups.
3. The method for preparing the composite material according to any one of claims 1 to 2, characterized in that: The following steps are involved: (1) The bismuth precursor is first loaded onto a titanium dioxide support by an electrostatic self-assembly method, and a heterojunction is obtained by hydrothermal synthesis; (2) cross-linking the heterojunction to the nanocellulose by chemical cross-linking to obtain a composite material; (3) The composite material is pre-treated by freezing with liquid nitrogen and freeze-dried into aerogel in a freeze dryer.
4. The method for preparing the nanocellulose aerogel composite material according to claim 3, characterized in that: In step (1), the total mass of the bismuth precursor and titanium dioxide accounts for 1.5-2.0% of the mass of deionized water.
5. The method for preparing a nanocellulose aerogel composite material according to claim 4, characterized in that: Bismuth nitrate pentahydrate was dispersed in deionized water, anatase titanium dioxide was added and magnetically stirred for 24 hours, and then the mixture was dried and calcined at a high temperature of 400°C for 5 hours.
6. The method for preparing the nanocellulose aerogel composite material according to claim 3, characterized in that: In step (2), the nanocellulose is a nanocellulose aqueous solution with a concentration of 0.65-1 wt %; a certain PVA solution is added with a concentration of 0.05 g / mL; glutaraldehyde is a cross-linking agent with a volume of 5-10 mL.
7. The method for preparing the nanocellulose aerogel composite material according to claim 6, characterized in that: The nanocellulose solution and the PVA solution were mixed and stirred for 1 h, glutaraldehyde solution was added and stirred for another 1 h, and then the heterojunction dispersion was added dropwise, cross-linked for 3 h, and washed three times by centrifugation with deionized water.
8. The method for preparing a nanocellulose aerogel composite material according to claim 3, characterized in that: The pretreatment temperature in step (3) is -196°C for 5-7 minutes; the freeze-drying temperature is -50-60°C for 24-30 hours.
9. Use of the nanocellulose aerogel composite material as claimed in claim 1 in photocatalytic degradation of antibiotic wastewater.
10. The use according to claim 9, characterized in that The nanocellulose aerogel composite material is put into a tetracycline solution with a concentration of 10-40 mg / L. The dosage of the composite material is selected to be 10, 30, 50 and 70 mg. The tetracycline solution is stirred under the irradiation of an ultraviolet light source to perform a photocatalytic degradation reaction; the ultraviolet light source used is a xenon lamp.
